New material-based liquid medicine for corrosive textures of automotive interiors and production process of novel material-based liquid medicine

By using corrosion texture agent prepared by new materials in automotive interior surface treatment, combined with the synergistic effect of nanocatalysts and nanofillers, the problems of uneven texture, poor durability and poor dispersion of nanomaterials are solved, and high-precision texture is achieved Control, durability improvement and self-healing capabilities are enhanced.

CN119392253APending Publication Date: 2025-02-07MOLD-TECH (DONGGUAN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411473693.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing automotive interior surface treatment technology has problems such as uneven texture effect, poor durability, lack of self-repair ability and poor dispersion of nanomaterials.

Method used

Using new materials-based corrosion texture agents for automotive interiors, the formula includes solvents, corrosion agents, nanocatalysts, corrosion inhibitors, nanofillers, multifunctional additives, intelligent corrosion inhibitors and self-healing components, ensuring the nanomaterials through ultrasonic dispersion equipment. Evenly dispersed and improve surface durability and self-healing capabilities with intelligent corrosion inhibitors and self-healing ingredients.

Benefits of technology

It realizes precise control of surface texture during corrosion, improves surface durability and self-repair ability, ensures uniform dispersion of nanomaterials, and significantly improves the service life and appearance retention of interior materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392253A_ABST
    Figure CN119392253A_ABST
Patent Text Reader

Abstract

The invention relates to the field of automobile manufacturing and surface treatment, and discloses an automobile interior corrosion texture liquid medicine based on a new material. The liquid medicine comprises the following components in percentage by weight: 40-60% of a solvent, 10-20% of a corrosive agent, 0.5-3% of a nano catalyst, 1-3% of a corrosion inhibitor, 0.5-5% of a nano filler, 0.5-3% of a multifunctional additive, 1-2% of an intelligent corrosion inhibitor and 0.5-3% of a self-healing component. By adopting the technical scheme of synergistic effect of the nano-catalyst and the nano-filler, the technical effect of accurately controlling the formation of the surface texture in the corrosion process is achieved through the acceleration effect of the nano-catalyst and the uniform distribution characteristic of the nano-filler, and compared with the technical scheme depending on a single corrosive agent in the prior art, the technical scheme of the invention has the advantages that the surface texture is accurately controlled; by means of the method, the technical problems that in a traditional method, surface corrosion textures are not uniform, the textures are not uniform in depth, and the machining effect is difficult to accurately control are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of automobile manufacturing and surface treatment, in particular to an automobile interior corrosion texture potion based on a new material and a production process thereof. Background Art

[0002] In the automotive manufacturing industry, the aesthetics and durability of automotive interiors are of great significance to improving the quality of the entire vehicle and user experience. To this end, the processing technology of automotive interior surfaces continues to develop to achieve more complex and exquisite surface texture effects. However, the existing technology still has certain deficiencies in this field, which are specifically manifested in the following aspects:

[0003] First, the traditional surface treatment process mainly relies on the chemical action of a single corrosive agent. Although this method can achieve texture processing on the interior surface to a certain extent, due to the lack of precise control of the corrosion process, it is easy to cause uneven texture effects and different depths of the surface. Especially when treating the surface of complex designs, it is difficult to achieve high-precision texture control. In addition, the corrosion speed and effect of a single corrosive agent are inconsistent on different materials, resulting in processing effects that are difficult to meet high-demand design requirements.

[0004] Secondly, the existing corrosion potion formulas usually cannot take into account both durability and self-healing ability. In actual use, the surface of automotive interior materials is often subjected to external forces such as friction and scratches, which requires that the surface treatment must not only be durable, but also have a certain self-healing ability when damaged. However, the corrosion potions in the prior art usually lack the regulatory effect of intelligent corrosion inhibitors and the addition of self-healing components, making the interior surface prone to texture wear and degradation after long-term use, seriously affecting the aesthetics and service life of the automotive interior.

[0005] Thirdly, the existing corrosion potions have poor adaptability under different environmental conditions. For example, fluctuations in temperature and humidity often affect the corrosion process, resulting in instability in the corrosion effect. Due to the single formula of traditional potions and the lack of multifunctional additives to adjust their physical and chemical stability, it is difficult to ensure consistent corrosion effects under variable production conditions. This defect not only leads to reduced production efficiency, but also affects the quality consistency of the final product.

[0006] Finally, the dispersibility of nanomaterials is also an important bottleneck in the existing technology. With the increasing application of nanomaterials in corrosion potions, how to ensure the uniform dispersion of nanoparticles has become a major challenge. Traditional mixing and dispersion methods are usually unable to overcome the characteristics of nanoparticles that are easy to agglomerate, resulting in uneven corrosion effects and even sedimentation and stratification. These problems not only affect the quality of the corrosion texture, but also increase the complexity and cost of the process.

[0007] Therefore, the present invention proposes an automobile interior corrosion texture potion based on new materials and a production process thereof to solve the deficiencies of the prior art. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides an automotive interior corrosion texture potion based on new materials and a production process thereof, which solves the problems existing in the prior art such as insufficient corrosion texture processing control accuracy, poor surface durability, lack of self-repairing ability, and uneven dispersion of nanomaterials.

[0009] To achieve the above purpose, the present invention is implemented by the following technical scheme: a car interior corrosion texture potion based on new materials, the potion includes the following components in weight percentage:

[0010] Solvent 40-60%;

[0011] Corrosive agent 10-20%;

[0012] Nano catalyst 0.5-3%;

[0013] Corrosion inhibitor 1-3%;

[0014] Nano filler 0.5-5%;

[0015] Multifunctional additive 0.5-3%;

[0016] Intelligent corrosion inhibitor 1-2%;

[0017] Self-healing ingredients 0.5-3%.

[0018] Preferably, the solvent is deionized water or ethanol.

[0019] Preferably, the corrosive agent is citric acid, phosphoric acid or sodium fluorosilicate.

[0020] Preferably, the nanocatalyst is nano titanium dioxide or nano zinc oxide.

[0021] Preferably, the nano filler is nano silicon dioxide or nano aluminum oxide, and the corrosion inhibitor is thiourea or benzotriazole.

[0022] Preferably, the self-healing component is a polymer or polyurethane encapsulated in microcapsules.

[0023] Preferably, the production process of the automotive interior corrosion texture potion based on the new material comprises the following steps:

[0024] S1, dissolving the corrosive agent in the solvent to form a uniform solution;

[0025] S2, gradually adding nanocatalysts and nanofillers into the solution, and using ultrasonic dispersion equipment to ensure uniform dispersion of nanoparticles;

[0026] S3, adding corrosion inhibitor, intelligent corrosion inhibitor, multifunctional additive and self-healing component, and stirring thoroughly;

[0027] S4. Use a membrane to filter the liquid medicine to remove incompletely dispersed particles and impurities;

[0028] S5. Testing the pH value, corrosion rate and nanomaterial dispersion of the solution;

[0029] S6. Seal and package the qualified medicine.

[0030] Preferably, the frequency of the ultrasonic dispersion equipment used in step S2 is 20-40 kHz, and the processing time is 30-60 minutes.

[0031] Preferably, the method for processing the surface of automobile interior with corrosion texture liquid comprises the following steps:

[0032] a) Clean the surface of automotive interior materials and remove oil stains and impurities;

[0033] b) Use spraying equipment to evenly apply the corrosion solution on the material surface;

[0034] c) Leave the sample at room temperature or low temperature for a period of time to allow the solution to fully react with the material surface to form a uniform corrosion texture;

[0035] d) Treat the residual liquid on the surface with a neutralizer and wash with deionized water;

[0036] e) Dry and post-treat the material surface.

[0037] Preferably, the neutralizing agent used in step d) is aqueous ammonia or sodium hydroxide solution, and the post-treatment includes coating a protective coating on the surface to enhance durability.

[0038] The present invention provides a new material-based automotive interior corrosion texture potion and a production process thereof. It has the following beneficial effects:

[0039] 1. The present invention adopts the technical solution of the synergistic effect of nanocatalysts and nanofillers, and achieves the technical effect of accurately controlling the formation of surface texture during the corrosion process through the acceleration of the nanocatalyst and the uniform distribution characteristics of the nanofillers. Compared with the technical solution relying on a single corrosive agent in the prior art, it is difficult to achieve a complex and uniform texture effect. The present invention effectively solves the technical problems of uneven surface corrosion texture, different depths of texture, and difficulty in accurately controlling the processing effect in the traditional method.

[0040] 2. The present invention adopts an innovative technical solution combining self-healing components with intelligent corrosion inhibitors. By intelligently controlling the corrosion rate during the corrosion process and realizing automatic repair of surface damage in subsequent use, the technical effect of enhancing the surface durability of interior materials and extending their service life is achieved. Compared with the technical solution in the prior art where the corrosion texture is easily damaged by the outside world and lacks repair ability, the present invention solves the problem of texture wear and surface degradation that is prone to occur on the interior surface during long-term use, and significantly improves the service life and appearance retention of interior materials.

[0041] 3. The present invention adopts an improved technical solution of multifunctional additives, which can maintain consistent corrosion effects under various environmental conditions by enhancing the physical and chemical stability of the solution, thus achieving the technical effect of significantly improving the applicability of the solution. Compared with the technical solution in the prior art, which has a single formula of the solution and is easily affected by ambient temperature, humidity and other external conditions, the present invention effectively solves the shortcomings of the traditional corrosion process, which is unstable corrosion effect and difficult to adapt to changing production conditions, thereby ensuring the stability and consistency of product quality.

[0042] 4. The present invention uses ultrasonic dispersion equipment to optimize the uniform distribution of nanoparticles. Through the action of high-frequency ultrasound, the uniform dispersion of nanocatalysts and nanofillers in the potion is ensured, achieving the technical effect of improving the stability and dispersibility of the potion. Compared with the technical solution in the prior art that nanomaterials have poor corrosion effects due to particle agglomeration, the present invention solves the problems of easy sedimentation of nanoparticles, potion stratification, and uneven corrosion effects in traditional formulas, and significantly improves the reliability of the corrosion process and the surface quality of the final product. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is the production process flow chart of automotive interior corrosion texture potion based on new materials. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Example:

[0046] Please see attached Figure 1 :

[0047] Example 1: Preparation of corrosion texture solution with synergistic effect of nanocatalyst and nanofiller

[0048] Material:

[0049] Solvent: Deionized water 50%

[0050] Corrosive agent: citric acid 15%

[0051] Nano catalyst: Nano titanium dioxide (TiO2) 1.5%

[0052] Corrosion inhibitor: benzotriazole 2%

[0053] Nano filler: Nano silicon dioxide (SiO2) 2%

[0054] Multifunctional additive: Polyethylene glycol 2%

[0055] Smart Corrosion Inhibitor: Picolinic Acid 1.5%

[0056] Self-healing ingredients: Microencapsulated polyurethane 2%

[0057] Process steps:

[0058] Dissolve the corrosive agent: Dissolve 15% citric acid in 50% deionized water and stir at room temperature for 20 minutes using a mechanical stirrer to ensure complete dissolution and form a homogeneous solution.

[0059] Adding nanomaterials: 1.5% nano titanium dioxide and 2% nano silicon dioxide were gradually added to the solution, and an ultrasonic dispersion device with a frequency of 30 kHz was used for 45 minutes to ensure that the nanoparticles were evenly dispersed.

[0060] Add other ingredients: 2% benzotriazole, 1.5% picolinic acid, 2% polyethylene glycol and 2% microcapsule-encapsulated polyurethane are added in sequence and stirred for 30 minutes to ensure that the ingredients are fully mixed.

[0061] Filtration and testing: Use a 0.2 micron filter membrane to filter the solution to remove incompletely dispersed particles and impurities. Then perform pH value, corrosion rate and nanomaterial dispersion tests to ensure that the solution meets the design standards.

[0062] Sealed packaging: The qualified medicine should be sealed and stored in a cool and dry place.

[0063] Summary of the embodiment: This embodiment achieves highly accurate corrosion texture control in the surface processing of automotive interior through the synergistic effect of nanocatalysts and nanofillers, and the generated surface texture is complex and uniform, and the depth is consistent. Compared with the traditional technical solution of a single etchant, this embodiment significantly improves the accuracy and consistency of texture processing.

[0064] Example 2: Preparation of corrosion texture potion combining self-healing component and smart corrosion inhibitor

[0065] Material:

[0066] Solvent: Ethanol 50%

[0067] Etching agent: Phosphoric acid 12%

[0068] Nano catalyst: Nano zinc oxide (ZnO) 2%

[0069] Corrosion inhibitor: Thiourea 1.5%

[0070] Nano filler: Nano alumina (Al2O3) 1%

[0071] Multifunctional additive: Acrylate 2%

[0072] Intelligent corrosion inhibitor: benzimidazole 1%

[0073] Self-healing ingredient: Microencapsulated polymer 2.5%

[0074] Process steps:

[0075] Dissolve the corrosive agent: Dissolve 12% phosphoric acid in 50% ethanol and stir until completely dissolved to form a uniform solution.

[0076] Add nanomaterials: gradually add 2% nano zinc oxide and 1% nano aluminum oxide, and use ultrasonic dispersion equipment with a frequency of 25kHz for 60 minutes to ensure uniform dispersion.

[0077] Add other ingredients: 1.5% thiourea, 1% benzimidazole, 2% acrylate and 2.5% microcapsule-encapsulated polymer were added in sequence and stirred for 30 minutes to ensure that the ingredients were evenly mixed.

[0078] Filtration and testing: Use a 0.5 micron filter membrane to filter the solution to remove undispersed particles and impurities. Test the pH value, corrosion rate and dispersibility of the solution.

[0079] Sealed packaging: Qualified medicines are sealed and stored in a low-temperature and dry environment.

[0080] Summary of the embodiment: By combining the self-healing component with the intelligent corrosion inhibitor, this embodiment can intelligently adjust the corrosion rate during the corrosion process and automatically repair the surface damage in subsequent use, significantly improving the durability and service life of the interior surface. Compared with the surface treatment effect of traditional potions, this embodiment provides higher surface durability and longer service life.

[0081] Example 3: Preparation of corrosion texture solution with multifunctional additives to enhance stability

[0082] Material:

[0083] Solvent: deionized water 45%

[0084] Etching agent: Sodium fluorosilicate 18%

[0085] Nano catalyst: Nano titanium dioxide (TiO2) 1%

[0086] Corrosion inhibitor: benzotriazole 2.5%

[0087] Nano filler: Nano silicon dioxide (SiO2) 3%

[0088] Multifunctional additive: polyurethane 2%

[0089] Intelligent corrosion inhibitor: dimethyl sulfoxide 1.5%

[0090] Self-healing ingredients: Microencapsulated polyurethane 2%

[0091] Process steps:

[0092] Dissolve the etchant: Dissolve 18% sodium fluorosilicate in 45% deionized water and stir until completely dissolved.

[0093] Add nanomaterials: gradually add 1% nano titanium dioxide and 3% nano silicon dioxide, and use ultrasonic dispersion equipment with a frequency of 35kHz for 30 minutes to ensure uniform dispersion.

[0094] Add other ingredients: 2.5% benzotriazole, 1.5% dimethyl sulfide, 2% polyurethane and 2% microencapsulated polyurethane in sequence, stirring for 30 minutes to ensure that the ingredients are fully mixed.

[0095] Filtration and testing: Use a 0.2 micron filter membrane to filter the solution to remove undispersed particles. Test the pH value, corrosion rate and stability of the solution.

[0096] Sealed packaging: seal the qualified medicine and store it at room temperature.

[0097] Summary of the embodiment: This embodiment uses a multifunctional additive to greatly enhance the stability of the solution under different temperature and humidity environments, ensuring the consistency and reliability of the corrosion effect. Compared with traditional solutions, the solution of this embodiment shows better adaptability under variable production conditions, ensuring the high quality consistency of the product.

[0098] Comparative experiment:

[0099] Experiment 1: Comparison of corrosion texture processing control accuracy

[0100] Existing technical solutions:

[0101] A single phosphoric acid was used as the etchant, without using nano-catalysts and nano-fillers.

[0102] The solvent is deionized water, the formula is simple, and it does not contain smart corrosion inhibitors and multifunctional additives.

[0103] Prior art formula:

[0104] Phosphoric acid 20%

[0105] Deionized water 80%

[0106] Experimental process:

[0107] Prior art experimental process: spray the prior art solution evenly on the surface of the automobile interior material, and let it stand at room temperature for 30 minutes to form a corrosion texture.

[0108] Experimental process of the present invention: The liquid medicine of Example 1 is evenly sprayed on the surface of the same material and left to stand for 30 minutes under the same conditions.

[0109] Comparison results:

[0110]

[0111] Result analysis: Example 1 significantly improves the uniformity and depth consistency of the surface texture through the synergistic effect of the nanocatalyst and the nanofiller, while the comparative group 1 shows poor control accuracy due to the lack of these components. The complex and uniform surface texture effect of Example 1 proves the advantages of the present invention.

[0112] Experiment 2: Surface durability comparison

[0113] Existing technical solutions:

[0114] Uses a traditional single-corrosive agent formula without self-healing ingredients and smart corrosion inhibitors.

[0115] Prior art formula:

[0116] Phosphoric acid 20%

[0117] Deionized water 80%

[0118] Experimental process:

[0119] Prior art experimental process: spray the prior art solution on the surface of the interior material, perform 100 friction tests after drying, and measure the degree of surface wear.

[0120] The experimental process of the present invention is as follows: the liquid medicine of Example 2 is sprayed on the same material surface, and the same friction test is performed after drying.

[0121] Comparison results:

[0122] Experiment number Potion recipes Number of tests Surface wear degree Example 2 Phosphoric acid + ZnO 100 Minor wear Comparison group 2 Phosphoric acid + deionized water 100 Visible wear

[0123] Result analysis: Example 2 showed significant durability in the friction test by adding self-healing components and intelligent corrosion inhibitors, while the comparative group 2 showed obvious wear due to the lack of these components. The results show that the present invention greatly improves the durability of interior materials.

[0124] Experiment 3: Comparison of self-repair capabilities

[0125] Existing technical solutions:

[0126] Uses a traditional corrosive formula that does not contain self-healing ingredients.

[0127] Prior art formula:

[0128] Phosphoric acid 20%

[0129] Deionized water 80%

[0130] Experimental process:

[0131] Prior art experimental process: scratch a 0.1 mm deep scratch on the surface of the interior material treated by the prior art, and observe the scratch repair after 24 hours.

[0132] Experimental process of the present invention: the same scratch test is performed on the surface of the interior material treated in Example 2, and the scratch repair condition is observed after 24 hours.

[0133] Comparison results:

[0134] Experiment number Potion recipes Scratch Depth Self-repair effect Example 2 Phosphoric acid + ZnO + self-healing 0.1mm Fully restored Comparison group 3 Phosphoric acid + deionized water 0.1mm No fix

[0135] Result analysis: The material of Example 2 achieved complete repair of scratches within 24 hours, while the material of Comparative Group 3 had no repair effect, indicating that the self-healing component of the present invention has a significant ability to repair material surface damage, further enhancing the service life of the material.

[0136] Experiment 4: Comparison of dispersibility of nanomaterials

[0137] Existing technical solutions:

[0138] Use traditional stirring technology without using ultrasonic dispersion equipment.

[0139] Prior art formula:

[0140] Phosphoric acid 20%

[0141] Deionized water 80%

[0142] Nano Titanium Dioxide 2%

[0143] Nano Silica 3%

[0144] Experimental process:

[0145] The experimental process of existing technology is: the nanomaterials are mixed with other ingredients in a solution, and the dispersion effect is observed after stirring with traditional stirring equipment for 30 minutes.

[0146] Experimental process of the present invention: The formula material of Example 3 is treated with an ultrasonic dispersion device for 30 minutes and then the dispersion effect is observed.

[0147] Comparison results:

[0148] Experiment number Potion recipes Dispersed equipment Dispersion test Example 3 Sodium fluorosilicate + SiO2 ultrasound Evenly dispersed Comparison group 4 Sodium fluorosilicate + SiO2 Mixing equipment Reunion is obvious

[0149] Result analysis: Example 3 significantly improves the uniformity of nanomaterial dispersion by using ultrasonic dispersion equipment and avoids agglomeration, while the comparative group 4 uses only traditional stirring equipment, resulting in uneven dispersion of nanomaterials and obvious agglomeration. The present invention has significant advantages in the dispersion of nanomaterials.

[0150] Experimental data table:

[0151]

[0152] Summary: The results of these examples and comparative experiments show that the present invention is significantly superior to the prior art in terms of corrosion texture processing control accuracy, surface durability, self-repairing ability, and nanomaterial dispersion. Each example demonstrates different technical advantages, and combined with specific experimental data, it proves the improvement of the present invention compared with the traditional technology. These improvements not only improve the accuracy and stability of the processing technology, but also extend the service life of the material, and have broad application prospects.

[0153] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. The car interior corrosion texture potion based on new materials is characterized by: The medicine solution includes the following components in percentage by weight: Solvent 40-60%; Corrosive agent 10-20%; Nano catalyst 0.5-3%; Corrosion inhibitor 1-3%; Nano filler 0.5-5%; Multifunctional additive 0.5-3%; Intelligent corrosion inhibitor 1-2%; Self-healing ingredients 0.5-3%.

2. The automotive interior corrosion texture potion based on new materials according to claim 1 is characterized in that: The solvent is deionized water or ethanol.

3. The automotive interior corrosion texture potion based on new materials according to claim 1 is characterized in that: The corrosive agent is citric acid, phosphoric acid or sodium fluorosilicate.

4. The automotive interior corrosion texture potion based on new materials according to claim 1 is characterized in that: The nano catalyst is nano titanium dioxide or nano zinc oxide.

5. The automotive interior corrosion texture potion based on new materials according to claim 1 is characterized in that: The nano filler is nano silicon dioxide or nano aluminum oxide, and the corrosion inhibitor is thiourea or benzotriazole.

6. The automotive interior corrosion texture potion based on new materials according to claim 1 is characterized in that: The self-healing component is a polymer or polyurethane wrapped in microcapsules, and the intelligent corrosion inhibitor is picolinic acid, benzimidazole or dimethyl sulfide.

7. The production process of the automotive interior corrosion texture potion based on new materials according to claims 1-6 is characterized in that: The following steps are involved: S1. dissolving the corrosive agent in the solvent to form a uniform solution; S2, gradually adding nanocatalysts and nanofillers into the solution, and using ultrasonic dispersion equipment to ensure uniform dispersion of nanoparticles; S3, adding corrosion inhibitor, intelligent corrosion inhibitor, multifunctional additive and self-healing component, and stirring thoroughly; S4. Use a membrane to filter the liquid medicine to remove incompletely dispersed particles and impurities; S5. Testing the pH value, corrosion rate and nanomaterial dispersion of the solution; S6. Seal and package the qualified medicine.

8. The production process of the new material-based automotive interior corrosion texture potion according to claim 7 is characterized in that: The frequency of the ultrasonic dispersion equipment used in step S2 is 20-40 kHz, and the treatment time is 30-60 minutes.

9. A method for processing the surface of automobile interior trim using the corrosion texture solution of claim 1, characterized in that: The following steps are involved: a) Clean the surface of automotive interior materials and remove oil stains and impurities; b) Use spraying equipment to evenly apply the corrosion solution on the material surface; c) Leave it at room temperature or low temperature for a period of time to allow the solution to fully react with the material surface to form a uniform corrosion texture; d) Treat the residual liquid on the surface with a neutralizer and wash with deionized water; e) Dry and post-treat the material surface.

10. The method for processing the surface of automobile interior with corrosion texture liquid according to claim 9, characterized in that: The neutralizing agent used in step d) is aqueous ammonia or sodium hydroxide solution, and the post-treatment includes coating a protective coating on the surface to enhance durability.